The Influence Of Marketing Mix And Brand Image On Impulsive Buying Of Camille Beauty Products On Tiktok Shop With Emotional Response As A Mediating Variable - Siti Nuraeni Pristiawati; Moch. Rizal; Lela Nurlaela Wati (Riviera Publishing, 2025)
The growth of TikTok Shop as a shopping platform has driven impulsive buying behavior, especially for beauty products such as Camille Beauty. This study aims to analyze the effect of the marketing mix and brand image on impulsive buying, with emotional response as a mediating variable. A quantitative method with PLS-SEM analysis was applied to 152 respondents who are Camille Beauty consumers on TikTok Shop in Jakarta. The results show that marketing mix and brand image significantly influence emotional response and impulsive buying. Emotional response also mediates the relationship between marketing mix and impulsive buying, but not the relationship between brand image and impulsive buying. This study highlights the importance of emotional strategies in short-video-based digital marketing.